Service-Learning in Environmental Education of Primary Preservice Teachers: Advancing SDGs and Improving Attitudes Towards Sustainable Development - María Diez-Ojeda; Marián Queiruga-Dios; Miguel Ángel Queiruga-Dios (Education Sciences)
This research analyzes the effect of implementing a Service-Learning (SL) program in the Environmental Education (EE) subject of the Primary Education Degree. The SL project was evaluated and the change in Attitudes towards Sustainable Development (ASD) of 44 preservice teachers was measured, considering Environment, Economy, Society, and Education as dimensions, using a pretest-posttest experimental design with no control group. The assessment of the SL project was favorable in all items (the purpose of the project, the training aspects, and the logistical and institutional aspects) and a significant improvement in ASD was observed in all dimensions. No significant differences were found in ASD based on the gender variable. It can be concluded that the inclusion of SL projects in the EE program significantly improves ASD while aligning education with the SDGs.